Readiness of Study Programs in Achieving Superior Accreditation Ratings: An Analysis Using the CIPPO Evaluation Model - Asyari, Hasyim; Sukarti, Dewi; Ratnaningsih, Sita; Azizah, Nurul Rizqi (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2023)
AbstractThis study explores the readiness of study programs to meet the nine-criteria policy set by the National Accreditation Agency for Higher Education (NAAHE/BAN-PT) in Indonesia and identifies strategies for achieving superior accreditation ratings. Using a qualitative case study approach, the research involved document analysis, observations, and in-depth interviews with fifteen key stakeholders. Data were analyzed through the CIPPO evaluation model. The findings reveal that: 1) the task force team meticulously prepared for the accreditation process across all stages; 2) effective coordination exists between university leaders, faculties, and study program teams; 3) accreditation criteria are clearly outlined with relevant and valid data; 4) all CIPPO elements are fulfilled, although student research integration remains suboptimal; 5) achieving superior accreditation enhances the university’s image and motivates further development in higher education, especially globally. Since the implementation of the nine-criteria policy in 2019, only one study program within the Ministry of Religion's Islamic Religious Universities has achieved superior accreditation, highlighting the significant challenges faced. Continuous improvement of the tridharma of higher education and expand cooperation both nationally and internationally.AbstrakPenelitian ini menggali kesiapan program studi dalam memenuhi kebijakan sembilan kriteria yang ditetapkan oleh Badan Akreditasi Nasional Perguruan Tinggi (BAN-PT) di Indonesia dan mengidentifikasi strategi untuk mencapai peringkat akreditasi unggul. Dengan pendekatan studi kasus kualitatif, penelitian ini melibatkan analisis dokumen, observasi, dan wawancara mendalam dengan lima belas pemangku kepentingan kunci. Data dianalisis menggunakan model evaluasi CIPPO. Temuan mengungkapkan bahwa: 1) tim task force mempersiapkan proses akreditasi dengan teliti di semua tahap; 2) terdapat koordinasi efektif antara pimpinan universitas, fakultas, dan tim program studi; 3) kriteria akreditasi dijelaskan dengan jelas dengan data yang relevan dan valid; 4) semua elemen CIPPO terpenuhi, meskipun integrasi penelitian mahasiswa masih kurang optimal; 5) pencapaian akreditasi unggul meningkatkan citra universitas dan memotivasi pengembangan pendidikan tinggi lebih lanjut, khususnya di tingkat global. Sejak implementasi kebijakan sembilan kriteria pada tahun 2019, hanya satu program studi di lingkungan Perguruan Tinggi Agama Islam Kementerian Agama yang meraih akreditasi unggul, menyoroti tantangan signifikan yang dihadapi. Peningkatan kualitas tridharma perguruan tinggi dan memperluas kerja sama baik nasional maupun internasional. How to Cite: Asy'ari, H., Sukarti, D., Ratnaningsih, S., Azizah, N.R., (2023).Readiness of Study Programs in Achieving Superior Accreditation Ratings: An Analysis Using the CIPPO Evaluation Model. TARBIYA: Journal of Education in Muslim Society, 10(2), 237-250. doi:10.15408/tjems.v10i2.38392.